Microascus microspora sp. nov. and Tolypocladium terrae sp. nov.; Two Novel Fungal Species Isolated from Soil in Korea - Seong-Keun Lim; Das Kallol; Jun-Woo Choi; Min-Gyu Kim; Chang-Gi Back; In-Kyu Kang; Seung-Yeol Lee; Hee-Young Jung (Mycobiology)
During an investigation of microfungi from various ecosystems in South Korea, two novel fungal species (KNUF-22-094T and KNUF-23-321CT) were discovered within the genera Microascus and Tolypocladium. The strain KNUF-22-094T stands out among other Microascus species due to its distinctive conidiogenous cells and conidial size ranges. The conidiogenous cells of KNUF-22-094T measured 2.3–4.3 × 2.0–3.6 µm, notably smaller than those of M. rothbergiorum (7.5–11.5 × 2.5–4.5 µm), M. sparsimycelialis (5.0–10.0 × 3.0–5.0 µm), which is considerably larger in both dimensions. For the conidial structures, conidia measured 2.6–4.8 × 2.6–4.4 µm, falling within a distinct range that is smaller than those of M. rothbergiorum (4.0–5.5 × 3.5–4.5 µm), M. verrucosus (5.0–7.0 × 4.5–6.0 µm), and M. restrictus (4.5–6.0 × 4.0–5.5 µm), but comparable in size to M. murinus, which tends to be more elongated (4.0–6.0 × 1.5–1.9 µm). The phialides of KNUF-23-321CT are globose, with a notably broad length range of 3.7–22.5 µm and a width of 0.9–1.5 µm, making it one of the most variable in length compared to species like T. album (3.5–10 µm) and T. endophyticum (1.3 ± 0.2 µm, 4.1 µm on average). Phylogenetic analyses using a multi-locus sequences supported to confirm their distinctness under the genus Microascus and Tolypocladium species. Thus, these fungal strains isolated from soil in Korea are proposed as a novel species according to their characteristics and are named Microascus microspora sp. nov. and Tolypocladium terrae sp. nov. Detailed descriptions, illustrations, and phylogenetic data are provided to support the recognition of these new species.